The Managerialization of Higher Education in Germany and its Consequences: Changes in Job Advertisements for Professorships in German Universities, 1990 to 2010 - Lisa-Maria Gerhardt; Jan Goldenstein; Simon Oertel; Philipp Poschmann; Peter Walgenbach (Emerald Publishing Limited, 2023)
Higher education institutions have undergone a transformation over the past few decades, from loosely coupled systems to more centrally managed organizations. Central to this ongoing development is the increasing competition for resources and reputation, driving higher education institutions to rationalize their structures and practices. In our study, we focused on changes in job advertisements for professorships in Germany from 1990 to 2010. Findings showed that the requirements stipulated by universities for professorial positions have become increasingly differentiated (and measurable) over time. In this context, competitive aspects, such as third-party funding, international orientation, or publications, have particularly come to the fore and grown significantly in importance. We discuss these findings in light of an increasing managerialization of higher education institutions, which has a direct effect on collegiality. We argue that the differentiation of professorial job profiles leads to even more formalized appointment processes and may push collegial governance into the background.
10.1108/S0733-558X20230000086003; 10.1108/S0733-558X20230000086003; University Collegiality and the Erosion of Faculty Authority; EBP099697246